Post-traumatic thoracic scoliosis with rib head dislocation and intrusion into the spinal canal: a case report and review of literature - Kishen, Thomas J. (Springer-Verlag, 2010)
The objective of the study was to report a rare occurrence of dislocation and intrusion of two rib heads into the spinal canal at the convex apex of a post-traumatic thoracic scoliosis in an adult in the absence of any neurological impairment. A 47-year-old male presented with a slowly progressive, post-traumatic thoracic scoliosis and a mild aching sensation over the posterior chest wall. The lower limb neurology and bowel and bladder function were normal. There was no clinical evidence of neurofibromatosis. CT scans showed that the 8th and 9th ribs on the convex apex of the scoliotic curve had intruded into the spinal canal and were lying adjacent to the dura and spinal cord. The MRI scan did not show any cord signal intensity changes. Although rib dislocation and intrusion into the spinal canal is uncommon, images should be carefully analysed to rule out this condition in sharp angular scoliotic curves.